2022
DOI: 10.3389/fmars.2022.591759
|View full text |Cite
|
Sign up to set email alerts
|

Dinoflagellate Assemblages in the West Iberian Upwelling Region (Sagres, Portugal) During 1994–2001

Abstract: Changes in the composition of dinoflagellates from 1994 to 2001 at a station influenced by wind-induced seasonal upwelling off SW Portugal were analyzed in relation to oceanography. 194 taxa of dinoflagellates were detected, the most frequent belonged to the genera Tripos, Protoperidinium, Dinophysis, Diplopsalopsis, Prorocentrum and Lingulodinium. The composition of dinoflagellate communities followed a seasonal pattern, in association with oceanographic forcing and change of upwelling conditions. Harmful spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Blanco [13] suggested that temperature controls the rate of cyst germination, while Peña-Manjarrez [50] pointed out that when water temperature increases to approximately 17 • C, a "thermal window" is reached for this species, promoting cyst germination, together with a decrease of their relative abundance in surface sediments. This role of temperature was also proposed by other authors within a temperature range from 17 to 23 • C [15, [50][51][52]. Maximum threshold temperature may change according to geographical area, but the minimum temperature reported for cyst germination is always 17 • C. This is the case observed in the Ria of Coruña, when below 17 • C the seawater column remains stable and stratified during summer [39] and bottom waters do not meet the temperature requirements for cyst development (Figure 3).…”
Section: Environmental Conditions Related To Bloom Events Of Lingulod...supporting
confidence: 80%
“…Blanco [13] suggested that temperature controls the rate of cyst germination, while Peña-Manjarrez [50] pointed out that when water temperature increases to approximately 17 • C, a "thermal window" is reached for this species, promoting cyst germination, together with a decrease of their relative abundance in surface sediments. This role of temperature was also proposed by other authors within a temperature range from 17 to 23 • C [15, [50][51][52]. Maximum threshold temperature may change according to geographical area, but the minimum temperature reported for cyst germination is always 17 • C. This is the case observed in the Ria of Coruña, when below 17 • C the seawater column remains stable and stratified during summer [39] and bottom waters do not meet the temperature requirements for cyst development (Figure 3).…”
Section: Environmental Conditions Related To Bloom Events Of Lingulod...supporting
confidence: 80%
“…Anschütz et al, 2022) as well as other Dinoflagellate species causing HABs in the North Atlantic (Gianella et al, 2021;Lima et al, 2022). These favourable conditions correspond to the spring-summer upwelling regime characterized by bright sunny days and nutrientrich cold waters, typical to the Iberian and Morocco coastal ocean (Ambar and Dias, 2008;Alvarez et al, 2010;Dıáz et al, 2013Dıáz et al, , 2016Moita et al, 2016;Leitão et al, 2019;Danchenko et al, 2022). In other locations on the North Atlantic, namely along the Bay of Biscay, British Isles and British Channel, the water is cold enough due to its higher latitude.…”
Section: Discussionmentioning
confidence: 98%
“…In other locations on the North Atlantic, namely along the Bay of Biscay, British Isles and British Channel, the water is cold enough due to its higher latitude. Consequently, the summer is the typical season for HAB of D. acuminata as well as other Dinoflagellate species in the North Atlantic (Smayda and Trainer, 2010;Dıáz et al, 2013Dıáz et al, , 2016Moita et al, 2016;Swan et al, 2018;Fernańdez et al, 2019;Gianella et al, 2021;Danchenko et al, 2022;Lima et al, 2022). Despite the environmental conditions favouring HABs being already reasonably understood, attempts to systematically forecast them have underachieve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course this has vindicated the efforts of the producers in their request to the monitoring authorities to reduce the areas for specific zones along the Algarve coast and has demonstrated the importance of liaison between the producers and the governing authorities. The situation with HAB monitoring in Sagres is presented in more detail by Danchenko et al (2019Danchenko et al ( , 2022.…”
Section: Monitoring For Habmentioning
confidence: 99%